Epithelial cells as alternative human biomatrices for comet assay - Rojas, Emilio; Lorenzo, Yolanda; Haug, Kristiane; Nicolaissen, Bjørn; Valverde, Mahara (Frontiers in Genetics, 2014)
The comet assay is a valuable experimental tool aimed at mapping DNA damage in human cells in vivo for environmental and occupational monitoring, as well as for therapeutic purposes, such as storage prior to transplant, during tissue engineering, and in experimental ex vivo assays. Furthermore, due to its great versatility, the comet assay allows to explore the use of alternative cell types to assess DNA damage, such as epithelial cells. Epithelial cells, as specialized components of many organs, have the potential to serve as biomatrices that can be used to evaluate genotoxicity and may also serve as early effect biomarkers. Furthermore, 80% of solid cancers are of epithelial origin, which points to the importance of studying DNA damage in these tissues. Indeed, studies including comet assay in epithelial cells have either clear clinical applications (lens and corneal epithelial cells) or examine genotoxicity within human biomonitoring and in vitro studies. We here review improvements in determining DNA damage using the comet assay by employing lens, corneal, tear duct, buccal, and nasal epithelial cells. For some of these tissues invasive sampling procedures are needed. Desquamated epithelial cells must be obtained and dissociated prior to examination using the comet assay, and such procedures may induce varying amounts of DNA damage. Buccal epithelial cells require lysis enriched with proteinase K to obtain free nucleosomes. Over a thirty year period, the comet assay in epithelial cells has been litlle employed, however its use indicates that it could be an extraordinary tool not only for risk assessment, but also for diagnosis, prognosis of treatments and diseases.